2008
DOI: 10.1177/001440290807400302
|View full text |Cite
|
Sign up to set email alerts
|

Culturally and Linguistically Diverse Students in Gifted Education: Recruitment and Retention Issues

Abstract: A persistent dilemma at all levels of education is the underrepresentation of African American, American Indian, and Hispanic/Latino students in gifted education and advanced placement (AP) classes. Research on the topic of underrepresentation has tended to focus on African American students, starting with Jenkins's (1936) study, which found that despite high intelligence test scores African American students were not formally identified as gifted. For over 70 years, then, educators have been concerned about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
252
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(262 citation statements)
references
References 51 publications
1
252
1
1
Order By: Relevance
“…Some of this gap may be due to differences in measured cognitive ability of students from different backgrounds and biases in these measures. However, the standard processes for gifted screening are based on teacher and parent referrals, and there is evidence of underreferral of qualified students from disadvantaged backgrounds-suggesting that teacher/ parent discretion in the referral process may be a further barrier (3)(4)(5)(6)(7). If so, then a comprehensive and objective screening program might be able to raise gifted participation rates among underserved groups by increasing their referral rates for gifted evaluation.…”
mentioning
confidence: 99%
“…Some of this gap may be due to differences in measured cognitive ability of students from different backgrounds and biases in these measures. However, the standard processes for gifted screening are based on teacher and parent referrals, and there is evidence of underreferral of qualified students from disadvantaged backgrounds-suggesting that teacher/ parent discretion in the referral process may be a further barrier (3)(4)(5)(6)(7). If so, then a comprehensive and objective screening program might be able to raise gifted participation rates among underserved groups by increasing their referral rates for gifted evaluation.…”
mentioning
confidence: 99%
“…In particular, we demonstrate, using rigorous methods of empirical analysis on approximately 70,000 cases, that overall, whereas Black and Latino/a students take the test for gifted-and-talented admission at substantially lower rates than their White and Asian counterparts, the gap in test-taking rates is significantly smaller for those enrolled in public pre-K programs, where there is greater access to information about the gifted-and-talented programs and its test for admission. We likewise find the same results when comparing subgroups defined by students' family and neighborhood characteristics (e.g., students in free-lunch programs versus not, students who speak English at home versus not, students who come from recent immigrant families versus not, and students who come from neighborhoods that consist of a greater versus smaller percentage of Black and Latino/a families and of populations with college degrees or higher).Our study contributes to the literature by uncovering this important relationship between public pre-K and gifted-and-talented test taking and by extending the work of numerous researchers in the field of gifted education (e.g., Davis, 2010;Ford, 1998;Ford, Grantham, & Whiting, 2008;Kitano, 2003;Moore, Ford, & Milner, 2005) who have urged educators to collect and analyze data to identify variables that positively and negatively influence the recruitment of culturally and linguistically diverse students for gifted education. It also extends the work of numerous preschool equity researchers who have explored enrollment in public pre-K as a potential avenue to reducing gaps in achievement by focusing not on achievement but on attendance in public pre-K as a potential avenue to reducing gaps in test-taking rates for the NYC gifted-and-talented admissions test.…”
mentioning
confidence: 53%
“…However, research has shown that Latino students are more likely to attend ethnically and economically segregated schools of lower quality and are more likely to be tracked into less challenging classes than White students. Latino students are also overrepresented in special education classes and, along with students from other minority groups, are underrepresented in gifted and talented programs (Ford, Grantham, & Whiting, 2008). The differences in educational experiences are believed to greatly restrict the access that Latino students, especially ELL students, have to high quality instruction and opportunity to learn the core curriculum.…”
Section: Opportunity To Learnmentioning
confidence: 99%